Human Capital Theory: A Holistic Criticism. (September 2014) - Tan, Emrullah
Human capital theory has had a profound impact on a range of disciplines from economics to education and sociology. The theory has always been the subject of bitter criticisms from the very beginning, but it has comfortably survived and expanded its influence over other research disciplines. Not surprisingly, a considerable number of criticisms have been made as a reaction to this expansion. However, it seems that these criticisms are rather fragmented and disorganized. To bridge this gap and organize them in a systematic way, the present article takes a holistic approach and reviews human capital theory from four comprehensive perspectives focusing on the methodological, empirical, practical, and moral aspects of the theory.